PERBEDAAN GAYA KEPEMIMPINAN DAN GAYA KOMUNIKASI BERDASARKAN GENDER (Studi Komparatif Kepala Desa Sibanteng dan Kepala Desa Kalong I, Kabupaten Bogor) - Permata Nurul Aini, (2021)
It is common for men to have an active role in politics. It should be the same for women; but cases are often found regarding the lack of female intervention because, in the eyes of society, women are still the object of development, not the doer. Personality and gender (which contribute to the distribution of characteristics, roles, and positions of women and men in society) can affect a person's leadership style. The purpose of this study is to analyze the differences in the leadership styles and communication styles of Sibanteng's headman and Kalong I's headman based on gender. The theory used in this study is the leadership style theory of Bass. This study uses a comparative method. The results show that the two leadership styles used are not caused or influenced by gender stereotypes. In contrast to the existing gender stereotypes, Kalong I's headman (a woman), has more 'masculine' characters than Sibanteng's headman (a man). In a village government organization led by the headman of Sibanteng, communication is done openly (two-way communication); while in a village government organization led by the headman of Kalong I, communication is carried out openly (two-way communication) and structured.